Polymer Based Devices for Photonics on the Chip - Jandura, Daniel; Gaso, Peter; Pudis, Dusan (Communications - Scientific letters of the University of Zilina, 2017)
In this paper we present promising technology for preparation of photonic devices based on polymer materials on the chip. We designed 2D and 3D structures in CAD (computer-aided design) software and we used two-photon polymerization mechanism for direct writing of these structures to IP-Dip photoresist material. This paper also deals with experimental procedures for preparation of polymer photonic devices on the chip and a new way of light coupling to devices on the chip. Morphological properties of prepared devices were investigated by scanning electron microscope (SEM). As a result, transmission spectrum characteristic was measured.